Aluminum nanoscale order in amorphous Al92Sm8 measured by fluctuation electron microscopy - Stratton, W. G.; Hamann, J.; Perepezko, J. H.; Voyles, P. M.; Mao, X.; Khare, S. V. (My University, 2005)
Fluctuation electron microscopy sFEMd measurements and simulations have identified nanoscale aluminum-like medium-range order in rapidly quenched amorphous Al92Sm8 which devitrifies by primary Al crystallization. Al92Sm8 amorphized by plastic deformation shows neither Al nanoscale order, nor primary crystallization. Annealing the rapidly quenched material below the primary crystallization temperature reduces the degree of nanoscale Al order measured by FEM. The FEM measurements suggest that 10?20 diameter regions with Al crystal-like order are associated with primary crystallization in amorphous Al92Sm8, which is consistent with the quenched-in cluster model of primary crystallization.